Three essays on financial distress - Ashraf, Sumaira (2021)
Large corporate failures and scandals in recent years indicate the shortcomings of current risk assessment tools and highlight the need for more extensive research on predicting financial distress (FD). The main objective of this thesis, comprised of three independent essays, is to provide empirical evidence on the factors affecting financial distress of firms. The first essay compares the accuracy of traditional distress prediction models at predicting the early warning signs of financial distress. The results reveal that the prediction accuracy of models declines for both early and more progressed financially distressed firms, when applied to an emerging market, Pakistan. The study results suggest that the researchers and practitioners should periodically revise the distress prediction models to adjust them with the dynamic changes in the business environment. The second essay for the first time investigates the benefit of combining accounting, market-based and financial reporting quality (FRQ) measures to predict financial distress of the developed and emerging market firms, UK and Pakistan, respectively. The resulting model shows good prediction accuracy for firms in the developed and emerging market, showing that the FRQ plays a significant role in the financial distress of firms. The findings of the study suggest that the researchers should use this hidden information of financial reports to predict financial distress of firms. The third essay explores the importance of board committee independence for firms operating in a developed market, the UK, and an emerging market, China. Our overall results support current best practice for corporate governance, which recommends more independent board members in compensation and nomination committees to ensure the unbiased selection and evaluation of corporate leadership; Três Ensaios sobre Empresas em Dificuldades Financeiras Resumo: Nos últimos anos observou-se a falência de grandes empresas, bem como vários escândalos financeiros, o que se tornou indicativo da existência de falhas ao nível das actuais ferramentas de avaliação de riscos, bem como da necessidade de estudos relacionados com a previsão da existência de empresas em dificuldades financeiras (FD). O principal objetivo desta tese, composta de três ensaios independentes, é fornecer evidências empíricas sobre os fatores que afetam as empresas em FD. O primeiro ensaio compara a exatidão dos modelos tradicionais de previsão de stress em prever os primeiros sinais de alerta de FD nas empresas. Os resultados revelaram que a exactidão da previsão dos modelos diminui no caso das empresas em fase inicial ou mais avançada de FD, quando aplicados ao mercado emergente Paquistão. Os resultados do estudo sugerem que tanto investigadores como profissionais devem periodicamente rever os modelos de previsão de FD por forma a os ajustar às mudanças dinâmicas do ambiente de negócios. O segundo ensaio investiga, pela primeira vez, o benefício da combinação de medidas contabilísticas, baseadas no mercado e na qualidade dos relatórios financeiros (FRQ), para prever se as empresas dos mercados desenvolvido e emergente, Reino Unido e Paquistão, respectivamente, se encontram em FD. O modelo final resultante mostra uma boa precisão de previsão para as empresas dos mercados desenvolvidos e emergentes, mostrando que a FRQ desempenha um papel significativo no FD das empresas. Os resultados do estudo sugerem que os investigadores devem usar essa informação, oculta dos relatórios financeiros, para prever o nível de FD das empresas. O terceiro ensaio explora a importância da independência do conselho do quadro de directores para as empresas que operam quer num mercado desenvolvido, Reino Unido, quer num mercado emergente, China. Os resultados globais fundamentam a prática da melhor governança empresarial, o que conduz à recomendação de um quadro de directores mais independente, ao nível dos comités de remuneração e nomeação, como forma de garantir uma selecção e avaliação da liderança empresarial não enviesadas.